Al-Qira'ah al-Shadzah and Its Influence on Language Orientation - Khairuddin Khairuddin (Institut Agama Islam Negeri (IAIN) Kendari, 2018)
This study aims to describe Qira'ah Shadzah and its role in continuity the dialect of Arabic, especially the verses related to Qira'ah Shadzah contained in chapter Al-Imran. This study used descriptive-normative and comparative methods. The results show that Qira'ah Shadzah made an important contribution in maintaining the continuity of Arab dialect. This is derived from the observation of some Qira'ah Shadzah because there is a change of vowel, such as the transfer from fathah to dhamma, from kasrah to dhamma, from fathah to kasrah, or from dhamma to kasrah. These changes show that Arab customs differ between desert people and civilized people. Where civilized people more often use fathah and kasrah because both are symbols of meekness, while on the other hand desert people prefer to use the dhammah which is a hard and rough symbol.